Sharp-Edges Steganography in Arabic Characters for Information Hiding - Roslan, Nuur Alifah (2011)
Steganography also known as covered writing creates attention in information hiding field in the past few years in the information security research area. Since the benefit towards this knowledge as the best way of covert communication, many methods and algorithms were implemented through Steganography. Even though many research were concern on image steganography, but in the past two years the text steganography had come with many algorithms and methods. There are two main issues arise in the text steganography: firstly, is a limited redundancy place to hide secret bit which lead to low capacity in hiding secret bits; and the second issue is to have a high invisibility stego-text document at the same time. In order to resolve the problem, sharp-edges stego method focusing in the individual Arabic characters as the redundant data. By using the sharp-edges for each Arabic character, each character in the cover text has possibility one to five places of hiding secret bits where, the number of sharp-edges is equals to the number of places to hide the secret bit. As a result, the capacity was increased up to 37.8% compared to the previous works and this method has high invisibility with 1.02 points over 10 points in invisibility ratio. Finally, the sharp-edges stego method had utilized the Arabic text for text steganography and this method also can be implemented to the same area of language such as Jawi, Persian or Urd